Emphasizing the “information” in BIM - Roux A. Addor, Miriam (2010)
The advent of BIM technology (Building Information Modeling), focused on design, construction and maintenance of buildings is generating significant changes in civil construction’s network. The process of designing and building sets out from bi-dimensional representation towards an n-dimensional reality. This is a movement towards the need to reduce errors in the work process due to the complexity of information exchange among players. This technology enables analysis, simulations and data gathering from the model, making all process information more reliable.